Pemanfaatan Teknologi Digital untuk Optimalisasi Penjualan Produk Lokal pada UMKM Dynala Food di Dusun Gentengan Desa Padang Kecamatan Singojuruh – Banyuwangi - Angga Ade Permana; Eka Pramodoningtyas; Lailatul Ikfia; Thoriqul Huda; Aula Safitri; Pita Dwi Agustin Tintania Putri; Diana Margareta; M Diki Andika; Heni Nailul Izzah; Ifau Himmatil Urfa; Helda Putra Dwi Kurnia (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
The primary purpose of this activity is to enhance the capabilities of micro, small, and medium enterprises (UMKM) in managing wet cake production in a more hygienic and efficient way in order to generate products with higher market value. The skill development emphasizes technical improvements in the production process by prioritizing cleanliness, food safety, and consistent quality, as well as increasing efficiency in the utilization of raw materials and labor. This activity was implemented for UMKM operating under Dynala Food in Gentengan Hamlet, Padang Village, Singojuruh District, Banyuwangi. In addition to production aspects, the program also aims to strengthen marketing strategies at both local and digital levels, enabling tofu and wet cake products to be more easily accessed by consumers. The implementation was conducted through door-to-door visits and direct field observations. The program stages included socialization, hands-on training, technology application, mentoring, evaluation, and achievement of program objectives. Focus Group Discussions (FGDs) were conducted to identify challenges, formulate concrete action plans, and support the adoption of technology and digitalization in business development.